(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article presents an analysis of the comedy «The Valencian Widow» by Lope de Vega, which vividly expresses the general state of Spain’s late start XVI – XVIIvekov. The new relationship, the idea of the emancipation of the individual from sredenevekovyh fetters of tradition and authority penetrated all life manifestations of Spanish society, including the family. The heroine of the play presents new trends; in the words and actions of the Renaissance felt an echo of the struggle for the emancipation of the human person. The focus of the article is made at the workshop intrigue characteristic of Lope de Vega, which carries the whole point of the play, creating its artistic atmosphere.